Intermedial textures: Gilberto Freyre: sociologist, poet, painter - Oliveira, Solange Ribeiro (2020)
Relying on the concepts of intermediality, ekphrasis and intermedial reference, the essay discusses Gilberto Freyre´s vast œuvre as that of a multiple artist, working in different áreas_ poetry, painting, literary prose_ as well as the author of groundbreaking contributions to the social sciences. The article especially underscores the close relationships between his output in the verbal and in the visual arts, remarkable for their constant reference to events, characters and landscapes analyzed in his sociological texts. In this context, the whole of Freyre´s production may be taken as a multiple, kaleidoscopic text, which, in different media, explores close- knit themes.